Rheological and sensorial behavior of tomato product enriched with pea protein and olive powder - Bal, Murad; Ates, Elif Gokcen; Erdem, Furkan; Tonyali Karsli, Gokcem; Karasu, Melis Cetin; Ozarda, Ozlem; Mert, Behic; Oztop, Mecit H. (Frontiers in Sustainable Food Systems, 2024)
In this study, a new functional product using Mediterranean ingredients (tomato, tomato peel powder and olive powder) was formulated where two different concentrations of protein (1 and 2%) and peel (2 and 4%) were tested. Olive powder was kept at a constant concentration of 2%. Physico-chemical, Rheological, and Sensorial analysis were carried out on the formulated samples. Soluble protein content was found as the highest in the sample containing 4% peel and 2% protein and it was affected by the pH and tomato peel concentration. Rheological results reveal shear-thinning behavior, as defined by the Herschel-Bulkley model, with protein and peel concentrations having a major influence on yield stress and viscosity. A positive trend was noticed between apparent viscosity and peel concentration, meantime protein concentration affected apparent viscosity adversely. Contrary relation between consistency index (k) values and apparent viscosity illustrate the complex interaction between protein and peel, particularly at higher concentrations. Furthermore, Principal Component Analysis (PCA) was used to investigate the complicated sensory landscape of tomato products with different quantities of pea protein and tomato peel. While higher tomato peel and protein levels have no direct impact on rheological qualities, they do add to astringency and sourness, which influences overall acceptability. Remarkably, the sample with the greatest quantities of peel and protein exhibits a delicate balance, with a loss in perceived tomato taste intensity and overall acceptability offsetting an increase in astringency. In terms of overall acceptability, the most preferred beverage was selected as the sample formulated with 2% peel and 1% protein.